The Effect of Influencer Credibility and Overclaims on Repurchase Intention Through Brand Trust in Scarlett Local Products - Nuri Divani Purba; Syifana Yukesha Mahda; Didik Gunawan; Mhd Sofian (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study aims to analyze the effect of influencer credibility and overclaim on repurchase intention through brand trust in local Scarlett products. The urgency of this study lies in providing a strategy for companies to understand the factors influencing consumers’ repurchase intention through influencer credibility, overclaim, and brand trust, as well as increasing consumers’ critical awareness of skincare product marketing information. This study employed an explanatory research design with a quantitative approach. The population consisted of 5,166,704 Instagram followers of Scarlett as of January 22, 2026. The sampling technique used non-probability sampling with an accidental sampling method, resulting in 100 respondents based on the Slovin formula. Data were collected through questionnaires and analyzed using Partial Least Square (PLS) with SmartPLS. The results showed that influencer credibility and overclaim had a significant effect on brand trust. Overclaim and brand trust significantly affected repurchase intention, while influencer credibility did not directly affect repurchase intention. In addition, influencer credibility and overclaim significantly affected repurchase intention through brand trust.